Auditoría de Gestión a la Asociación de Cafetaleros Ecológicos “APECAP”, ciudad de Palanda y Chinchipe, periodo 2022 - Vargas Mendieta, Mayer Nicol (2024)
The present article titled "Management Audit of the Ecological Coffee Growers Association 'APECAP,' in the city of Palanda and Chinchipe, for the year 2022" primarily aimed to evaluate the internal control system of the association by analyzing its efficiency, effectiveness, and economy in resource management and objective fulfillment. To conduct the management audit, a preliminary visit was made to APECAP's facilities. During this visit, relevant information and documentation were collected using various research methods, including scientific, analytical, inductive, and synthetic approaches. Additionally, techniques such as literature and document review, interviews, and observation were employed. These efforts facilitated the completion of Phases I and II: Preliminary Knowledge and Planning. Based on the gathered information, a detailed planning memorandum and a risk matrix were created to guide the audit's development. In Phase III, Execution, the audit program and questionnaire were implemented, assessing the internal control to determine the level of confidence and risk in the association's operations. The results of this evaluation were documented in narrative sheets, supported by corresponding evidence. Compliance with the Annual Operational Plan was verified by analyzing the most representative activities. Efficiency indicators (performance evaluations, training, professionalization levels), effectiveness indicators (knowledge of the mission, vision, objectives, and internal regulations), and economy indicators (budget execution of income and expenses) were also evaluated. Significant findings obtained during the audit will be detailed in a final report in Phase IV, which will include recommendations for improving APECAP's management. Finally, in Phase V, Follow-up, a schedule will be established to monitor compliance with these recommendations.